Is there a role for Islamic bonds in global diversification strategies? - Balcilar, Mehmet; Cerci, Gozde; Demirer, Riza (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to examine the international diversification benefits of Islamic bonds (Sukuk) for equity investors in conventional stock markets. The authors compare the diversification benefits of these securities with their conventional alternatives from advanced and emerging markets. Compared to conventional bonds, Sukuk are backed by tangible assets and carry both bond and stock-like features. Furthermore, the Sharia-based limitations limit the risk in these securities as a result of ethical investing rules. The regime-based model provides insight to possible segmentation (or integration) of these securities from global markets during different market states. Design/methodology/approach - Risk spillover effects across conventional and Islamic stock and bond markets are examined using a Markov regime-switching GARCH model with dynamic conditional correlations (MS-DCC-GARCH). Weekly return series for conventional (advanced and emerging) and Islamic stock and bond indices are examined within a regime-dependent specification that takes into account low, high, and extreme volatility states. The DCC are then used to establish alternative diversified portfolios formed by supplementing conventional and Islamic equities with conventional and Islamic bonds one at a time. Findings - Asymmetric shocks are observed from conventional stocks and bonds into Islamic bonds (Sukuk). Compared to emerging market bonds, Sukuk are found to display a different pattern in the transmission of global market shocks. The analysis of dynamic correlations suggests a low degree of association between Islamic bonds and global stock markets with episodes of negative correlations observed, particularly during market crisis periods. Portfolio performance analysis suggests that Islamic bonds provide valuable diversification benefits that are not possible to obtain from conventional bonds. Originality/value - This study provides comprehensive analysis of volatility interactions and dynamic correlations across Islamic and conventional markets within a regime-based framework and provides insight to whether these securities could serve as safe havens or diversifiers for global investors. The findings have significant implications for global diversification strategies, particularly during market crisis periods.
Keywords: Volatility spillover; International diversification; Dynamic correlations; Islamic bonds